Effects of school-based light intervention on daytime napping and daytime sleepiness among adolescents in Iceland - Ingibjörg Patricia Magnúsdóttir 1999- (2023)
The current study aimed to examine the effectiveness of a light intervention on daytime napping (DN) and daytime sleepiness (DS) among adolescents. The sample consisted of 195 participants in one upper-secondary school, randomized into three groups a bright light (BL) (n = 77), a dim light (DL) (n = 51) group, and a control group with standard light (SL) (n = 66). The light intervention used ceiling-mounted BL exposure that participants were exposed to for a whole school year with three measurement points, a baseline, and two follow-up measurements. The Cleveland Adolescent Sleepiness Questionnaire (CASQ) and the Napping Behaviour Questionnaire (NBQ) were used to assess participants' levels of DS and examine DN. Results from repeated ANOVA for DS showed no significant main effect between the three groups nor an interaction effect between different measurement points and groups. Binary logistic regression results for DN showed that light intervention did not associate with reduced DN. These preliminary findings suggest that light intervention did not reduce DS or DN among healthy adolescents as was proposed. However, further analyses should account for the study‘s missing data as well as explore moderators and mediators in this context. Keywords: daytime napping, daytime sleepiness, adolescents, light intervention, randomized control trial Í þessari íhlutunarrannsókn var kannað hvort ljósameðferð hefði áhrif á daglúra og dagsyfju meðal unglinga. Úrtakið samanstóð af 195 þátttakendum úr einum framhaldsskóla sem var slembiraðað í þrjá hópa, hóp sem fékk kald-hvíta lýsingu (e. bright white light) (n = 77), hóp sem fékk heit-hvíta lýsingu (e. dim white light) (n = 51) og samanburðarhóp sem fékk hefðbundna flúorlampalýsingu (n = 66). Notuð var innbyggð loftljósalýsing sem náði til allra þátttakenda yfir heilt skólaár, með þremur mælipunktum, grunnlínu og tveimur eftirfylgni mælingum. Til að meta dagsyfju og daglúra þátttakenda voru notaðir tveir spurningalistar: Cleveland Adolescent Sleepiness Questionnaire (CASQ) ...